2015
DOI: 10.1213/xaa.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management for Resection of Bilateral Pulmonary Artery Sarcoma

Abstract: We describe a patient who presented with a bilateral pulmonary artery sarcoma, initially treated as pulmonary embolism, that necessitated concomitant pulmonary endarterectomy and pneumonectomy. We reviewed the anesthetic management used for this procedure, which bears many similarities to the management of patients undergoing pulmonary thromboendarterectomy. Right ventricular failure, pulmonary hemorrhage, and cerebral ischemia due to circulatory arrest are life-threatening perioperative complications. The ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In our case, because of circulatory collapse after induction of general anesthesia, emergent median sternotomy was necessary to start ECC. In contrast, in the PPAS case report published by Hoogma et al [3], an increase in CVP or findings of right heart overload was not identified, and there was no mention of deterioration in circulation dynamics after induction of anesthesia.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In our case, because of circulatory collapse after induction of general anesthesia, emergent median sternotomy was necessary to start ECC. In contrast, in the PPAS case report published by Hoogma et al [3], an increase in CVP or findings of right heart overload was not identified, and there was no mention of deterioration in circulation dynamics after induction of anesthesia.…”
Section: Discussionmentioning
confidence: 75%
“…For bilateral PPAS, it is necessary to perform a pulmonary artery endarterectomy. This procedure requires deep hypothermia and circulation arrest to prevent backflow from bronchial arteries into the pulmonary artery [3]. For unilateral PPAS, diagnosed early, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TCA prevented backflow of blood via the bronchial arteries and thus gave better bloodless surgical field. [ 3 ] The PA catheter was placed in the PA by the surgeon so as not to injure the bare intima. It was possible to wean the patient off CPB on moderate inotropic support.…”
mentioning
confidence: 99%